Matcha Improves Metabolic Imbalance-Induced Cognitive Dysfunction. (29th November 2020) - Kim, Jong Min; Lee, Uk; Kang, Jin Yong; Park, Seon Kyeong; Kim, Jong Cheol; Heo, Ho Jin
Abstract : This study was conducted to assess the protective effect of extract of match (EM) on high-fat diet- (HFD-) induced cognitive deficits in male C57BL/6 mice. It was found that EM improved glucose tolerance status by measuring OGTT and IPGTT with HFD-induced mice. EM protected behavioral and memory dysfunction in Y-maze, passive avoidance, and Morris water maze tests. Consumption of EM reduced fat mass, dyslipidemia, and inflammation in adipose tissue. Also, EM ameliorated hepatic and cerebral antioxidant systems. EM improved the cerebral cholinergic system by regulating ACh contents and expression of AChE and ChAT. Also, EM restored mitochondrial function in liver and brain tissue. EM attenuated hepatic inflammatory effect, lipid synthesis, and cholesterol metabolism by regulating the protein expression of TNF- α, TNFR1, p -IRS-1, p -JNK, IL-1 β, iNOS, COX-2, HMGCR, PPAR γ, and FAS. Finally, EM regulated cognitive function and neuroinflammation in the whole brain, hippocampus, and cerebral cortex by regulating the protein expression of p -JNK, p -Akt, p -tau, A β, BDNF, IDE, COX-2, and IL-1 β . These findings suggest that EM might be a potential source of functional food to improve metabolic disorder-associated cognitive dysfunction.